RANCANG BANGUN SISTEM INFORMASI INVENTORY PLYWOOD BERBASIS WEB DI CV.JATI MAKMUR - teguh pradana; Muhammad m (STMIK YADIKA BANGIL, 2020)
Abstract : CV. Jati Makmur is a company engaged in the process of processed wood production (Wood Working) which all activities are still using the manual system. The purpose of research and manufacture of this application system is to help companies in facilitating the process of sales transactions and stock Plywood information. CV. Jati Makmur is implemented by creating a more optimized computerized application using DFD diagram for modeling application built using PHP, JavaScript, MySQL applications as database. The results of the development of an application that can improve the quality of sales transactions and sales report files and stock Plywood, and facilitate in the process of knowing customer identity search that can be done quickly, easily and in accordance with the needs of the company.This application can also make payment receipt in the form of a memorandum as proof of payment. After that proof of payment will be received by the warehouse with two copies of one received and signed by the warehouse, a duplicate submitted to the purchasing department to be signed Keywords: Inventory, Plywood,web,php,Mysql